REVIEW OF TOTAL QUALITY MANAGEMENT CONCEPT - Daniel Indarto Prajogo (Institute of Research and Community Outreach - Petra Christian University, 1999)
The definition of TQM continues to be a debated issue to organizational management. Not only is there an absence of a uniform definition but also there is no prescriptive standard outlining TQM concepts. This supports an argument that TQM is not merely a tool or method that is ready for use, but there is a set of underlying principles, philosophies and paradigms that must be applied in the unique organizational context. This paper will discuss the concept of TQM at three integrated levels in an organization from inside out; namely paradigm level, system and structural level and technical and operational level in the purpose for helping organizations to grasp the comprehensive substance of TQM.